Quality in e-Government services: A proposal of dimensions from the perspective of public sector employees. Issue 2 (May 2018) - Janita, M. Soledad; Miranda, F. Javier
Highlights: Research on high quality e-services is extended to the domain of the government's relationship with its employees, G2E. Quality in electronic services in the G2E context is a multidimensional construct. Four dimensions are identified to measure quality in the G2E context. The security dimension is the one considered most important by the participants in the study. Abstract: The main objective of the work is to identify the key factors that must be considered by the Government when designing the web service portals used by its employees. To achieve these objectives, empirical work was then carried out to collect primary information, using the Delphi method and obtaining the opinion of 31 specialists who are experts in quality management in the university environment. The results of the study show that four dimensions must be considered to measure the quality of electronic services. These dimensions are: quality of information, technical efficiency, privacy and communication with the employee.